A comparison study on gust factor considering non-stationary effects under typhoon and monsoon conditions. Issue 12 (September 2018) - Wang, Shouqiang; Zhao, Lin; Cao, Shuyang; Zhang, Yufeng; Yin, Feng; Ge, Yaojun
This article studies the feasibility and effectiveness of a non-stationary model using field measurements. Gust factors are compared for both typhoon and monsoon winds whose maximum 10-min mean wind speeds were all greater than 20 m/s using non-stationary models. Wind speeds were recorded by three-dimensional anemometers by the Structural Health Monitoring System of Xihoumen Bridge. The study focuses on the dependences of gust factor on gust averaging time, sample duration, and mean wind speed for both typhoon and monsoon climates. The gust factor curve and the relationship between gust factor and turbulence intensity are also studied. The results suggest that a non-stationary model is more suitable for actual turbulence flow, particularly under typhoon conditions. The article also compares resulting gust factor curves with those obtained in former studies and shows that accurate gust factor curves can be obtained by field measurements for monsoon wind. It is thus recommended that gust factor research should differentiate between typhoon and monsoon winds.